Nilai Perusahaan Di Tengah Dinamika Modal Dan Laba: Studi Empiris Sektor Konsumsi Yang Terdaftar Di Bursa Efek Indonesia - Ujang Kusnaedi; Atri Nodi Maiza Putra; Nurhayati Nurhayati (Benefit: Journal of Bussiness, Economics, and Finance, 2025)
This study aims to analyze the effect of capital structure and profitability on firm value in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. Capital structure is measured using the Debt to Asset Ratio (DAR), while profitability is measured using Return on Assets (ROA), and firm value is measured using Price to Book Value (PBV). This research adopts a quantitative approach using secondary data in the form of annual financial statements from 10 companies in the food and beverage subsector. The analysis method used is multiple linear regression to examine both the simultaneous and partial effects among the variables. The results indicate that capital structure and profitability simultaneously have a significant effect on firm value. Partially, profitability has a significant positive effect, whereas capital structure does not have a significant effect on firm value. These findings suggest that a company's ability to generate profit has a greater influence on market value compared to its financing composition.